2015
DOI: 10.1155/2015/247892
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin Overexpression Induced Tumor Progression and Chemoresistance to Oxaliplatin through Induction of Stem-Like Properties in Human Colorectal Cancer

Abstract: Colorectal cancer (CRC) is one of the most common and fatal malignancies worldwide. The poor prognosis of colorectal cancer patients is due to development of chemoresistance and cancer metastasis. Recently osteopontin (OPN) has been associated with stem-like properties in colorectal cancer. This study further examined the clinicopathological significance of OPN in CRC and its effect on chemoresistance and transcription of stem cell markers. We examined the transcription level of OPN in 84 CRC patients and corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 21 publications
3
36
0
2
Order By: Relevance
“…OPN has been shown to exert a positive effect on the modulation of stemness traits in hepatocellular carcinoma, lung cancer, colorectal cancer, and pancreatic cancer. [47][48][49][50] Figure 6 shows that OE-OPN neutralized the cinobufagininduced reduction in spheroid size and p-STAT3(Tyr727) along with p-STAT3(Ser705), Bax, Bcl-2, caspase-3, cleaved PARP, Nanog, Sox-2 and Oct3/4 levels. We also found that si-OPN plus cinobufagin treatment synergistically downregulated the expression of these indicators which suggested that OPN participates in the cinobufagininduced suppression of stemness features in osteosarcoma spheriods.…”
Section: Discussionmentioning
confidence: 99%
“…OPN has been shown to exert a positive effect on the modulation of stemness traits in hepatocellular carcinoma, lung cancer, colorectal cancer, and pancreatic cancer. [47][48][49][50] Figure 6 shows that OE-OPN neutralized the cinobufagininduced reduction in spheroid size and p-STAT3(Tyr727) along with p-STAT3(Ser705), Bax, Bcl-2, caspase-3, cleaved PARP, Nanog, Sox-2 and Oct3/4 levels. We also found that si-OPN plus cinobufagin treatment synergistically downregulated the expression of these indicators which suggested that OPN participates in the cinobufagininduced suppression of stemness features in osteosarcoma spheriods.…”
Section: Discussionmentioning
confidence: 99%
“…OPN is commonly found in some mineralized tissues as an extracellular matrix (ECM), and it also behaves as a secreted protein in body fluids, such as milk, blood, urine, saliva, seminal fluid and bile 58 . As a result of its diverse distribution, OPN is involved in multiple steps of tumor biology, including cell proliferation, survival, angiogenesis, chemoresistance, stem-like properties, tumor invasion, and metastasis 59 . Specifically, as referred to the publications through 2000 to 2015 with the keywords 'osteopontin AND cancer' on PubMed database, it is observed that elevated OPN expression in serum samples has been used as a prime mediator of various human cancers.…”
Section: The Involvement Of Opn In Tumor Biologymentioning
confidence: 99%
“…In their further work, the transcription level of OPN in 84 CRC patients was well characterized, and the overexpression of OPN in DLD1-OPN cells induced cell survival and chemoresistance to oxaliplatin treatment. Moreover, OPN overexpression was involved in tumor metastasis and the decrease of the survival rate of CRC patients, by inducing the stem-like property of CRC cells via overexpressing SOX2 59 , 68 .…”
Section: The Involvement Of Opn In Tumor Biologymentioning
confidence: 99%
“…Another interesting fact is that several studies have shown the deposition in human coronary arteries of osteopontin, a member of a category of the NCPs termed SIBLING (Small Integrin‐Binding Ligand, N‐linked Glycoprotein), which have been associated with atheroma calcification and tumors progression , besides other complications. Once the dentin and cementum present osteopontin and other SIBLING proteins in their composition, with similar role in mineralization and cellular adhesion; theoretically, some of these proteins released from dentin as result of orthodontic root resorption may also circulate through the body.…”
Section: Discussionmentioning
confidence: 99%